Seizure control as a new metric in assessing efficacy of tumor treatment in low-grade glioma trials. Issue 1 (20th September 2016) - Avila, Edward K.; Chamberlain, Marc; Schiff, David; Reijneveld, Jaap C.; Armstrong, Terri S.; Ruda, Roberta; Wen, Patrick Y.; Weller, Michael; Koekkoek, Johan A. F.; Mittal, Sandeep; Arakawa, Yoshiki; Choucair, Ali; et al.
Abstract: Patients with low-grade glioma frequently have brain tumor–related epilepsy, which is more common than in patients with high-grade glioma. Treatment for tumor-associated epilepsy usually comprises a combination of surgery, anti-epileptic drugs (AEDs), chemotherapy, and radiotherapy. Response to tumor-directed treatment is measured primarily by overall survival and progression-free survival. However, seizure frequency has been observed to respond to tumor-directed treatment with chemotherapy or radiotherapy. A review of the current literature regarding seizure assessment for low-grade glioma patients reveals a heterogeneous manner in which seizure response has been reported. There is a need for a systematic approach to seizure assessment and its influence on health-related quality-of-life outcomes in patients enrolled in low-grade glioma therapeutic trials. In view of the need to have an adjunctive metric of tumor response in these patients, a method of seizure assessment as a metric in brain tumor treatment trials is proposed.